Positive electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
The positive electrode for non-aqueous electrolyte secondary batteries, featuring controlled peak ratios and optimized active material properties, addresses the challenge of heat generation during short circuits, ensuring safety by minimizing thermal runaway.
Patent Information
- Application Number
- JP2021146507
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-08
- Publication Date
- 2025-11-06
- Estimated Expiration
- 2041-09-08
AI Technical Summary
Existing non-aqueous electrolyte secondary batteries face challenges in suppressing heat generation during sudden short circuits, particularly when connected in parallel, leading to a chain reaction of heat generation and potential safety hazards.
A positive electrode for non-aqueous electrolyte secondary batteries is designed with a layered compound and a phosphate compound having an olivine structure, where the ratio of specific peak half-widths in X-ray diffraction patterns is controlled, along with optimized tap density and median diameter of the second positive electrode active material to prevent excessive lithium ion diffusivity and reduce thermal runaway.
The solution effectively suppresses heat generation during sudden short circuits, reducing temperature rise, swelling, and preventing cracking or explosion, thereby enhancing safety.
Smart Images

Figure 0007765220000002 
Figure 0007765220000003 
Figure 0007765220000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In non-aqueous electrolyte secondary batteries, ions in the electrolyte are responsible for electrical conduction. Lithium secondary batteries, one type of non-aqueous electrolyte secondary battery, are installed as power sources in small electronic devices such as digital cameras and laptop computers, as well as in vehicles. Lithium secondary batteries are composed of a positive electrode, a negative electrode, and a separator. Of these, the positive electrode includes a positive electrode current collector and a positive electrode mixture layer coated on the surface of the positive electrode current collector and containing a positive electrode active material, a conductive material, and a binder.
[0003] Positive electrode active materials for non-aqueous electrolyte secondary batteries include LiFePO4 or olivine compounds in which a portion of the LiFePO4 is substituted with Mn; LiCoO2, LiNiO2, LiMnO2, LiCoNiO2, LiCoMO2, and LiNiMO2, in which some of the elements in these positive electrode active materials are substituted with other elements; and ternary layered compounds containing Co, Ni, or Mn. Layered compounds, in particular, offer high capacity and high voltage, making them suitable for applications where energy density is important. However, layered compounds have poor thermal stability in the charged state, making it difficult to suppress heat generation during short-circuiting when used in non-aqueous electrolyte secondary batteries. Therefore, to ensure the safety of non-aqueous electrolyte secondary batteries, techniques have been developed to blend layered compounds with LiFePO4 or olivine compounds in which a portion of the LiFePO4 is substituted with Mn. Olivine compounds in which a portion of LiFePO4 is substituted with Mn have operating potentials not significantly different from those of layered compounds, making blending them easier to ensure safety without significantly reducing energy density.
[0004] For example, in Patent Document 1, in order to obtain thermal stability, an olivine compound having a particle size of about 0.1 to 3 μm and occupying a volume fraction of 5 to 100% in a positive electrode active material is mixed with a layered compound such as a lithium metal oxide. Also, in Patent Document 2, a layered compound is mixed with an olivine compound having an average particle size smaller than that of the layered compound in a positive electrode active material. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6813487 [Patent Document 2] Patent No. 5574239 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the inventors of the present application have conducted research and found that these prior art technologies are insufficient in terms of the safety against sudden short circuits that is required of recent nonaqueous electrolyte secondary batteries. In particular, when multiple nonaqueous electrolyte secondary batteries are connected in parallel to form a battery pack, the resistance of the entire battery pack is reduced. Therefore, even if the same short circuit occurs, a short-circuit current tends to flow more rapidly than when a single nonaqueous electrolyte secondary battery is used. Therefore, a solution has been sought. Specifically, if the temperature of a nonaqueous electrolyte secondary battery becomes high enough to ensure separator meltdown, further short circuits will occur within the nonaqueous electrolyte secondary battery, leading to a chain reaction of heat generation. Therefore, there is a need for a nonaqueous electrolyte secondary battery that can suppress heat generation even when a sudden short circuit occurs.
[0007] The present invention has been made in view of the above, and an object of the present invention is to provide a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery that suppresses heat generation even when a sudden short circuit occurs. [Means for solving the problem]
[0008] In order to solve the above problems and achieve the object, the positive electrode for a non-aqueous electrolyte secondary battery according to the present invention is a positive electrode for a non-aqueous electrolyte secondary battery including a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector, wherein the positive electrode mixture layer includes a first positive electrode active material which is a layered compound represented by the general formula shown in the following formula (1), a second positive electrode active material which is represented by the general formula shown in the following formula (2) and has a carbon material film formed on the surface of a phosphate compound having an olivine structure, and a conductive material, and in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays for the positive electrode for a non-aqueous electrolyte secondary battery before being assembled into a non-aqueous electrolyte secondary battery, or for the positive electrode for a non-aqueous electrolyte secondary battery when the charge rate of the non-aqueous electrolyte secondary battery after being subjected to an initial activation treatment by charging and discharging for at least 1 cycle is 0%, the value P1 / P2 of the ratio between a first half-value width P1 of a peak attributed to the (003) plane of the first positive electrode active material having a diffraction angle of 18.0° or more and 19.0° or less and a second half-value width P2 of a peak attributed to the (101) plane of the second positive electrode active material having a diffraction angle of 20.0° or more and 21.0° or less is 0.30 or more and 1.00 or less. Li a Ni x Co y M1 1-x-y O2···(1) LiMn z M2 b Fe 1-z-b PO4···(2) However, in the above formula (1), M1 is at least one selected from Ti, Zr, Nb, W, P, Al, Mg, V, Mn, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, Cu, Ag, Ce, Pr, Ge, Bi, Ba, Er, La, Sm, Yb, Sb, Bi, S and Zn, and satisfies 0 < a ≦ 1.2, 0 < x ≦ 0.9, 0 < y ≦ 0.5, 0 < x + y < 1. In the above formula (2), M2 is at least one selected from Ni, Co, Ti, Cu, Zn, Mg, Zr, Ca, Y, Mo, Ba, Pb, Bi, La, Ce, Nd, Gd, Al, Ga and Sr, and satisfies 0 < z ≦ 0.9, 0 ≦ b ≦ 0.1, 0 < z + b < 1.
[0009] In the positive electrode for a non-aqueous electrolyte secondary battery according to the present invention, the second positive electrode active material may have a tap density of 0.7 g / cc or more and 1.00 g / cc or less.
[0010] In the positive electrode for a non-aqueous electrolyte secondary battery according to the present invention, the median diameter of the second positive electrode active material may be 1 / 100 to 1 / 5 of the median diameter of the first positive electrode active material.
[0011] In the positive electrode for a non-aqueous electrolyte secondary battery according to the present invention, the second positive electrode active material may have a median diameter of 0.1 μm or more and 1.0 μm or less.
[0012] In addition, in the positive electrode for a non-aqueous electrolyte secondary battery according to the present invention, in the above invention, the ratio of the weight of the second positive electrode active material to the total weight of the first positive electrode active material and the second positive electrode active material may be 10% or more and 30% or less.
[0013] A non-aqueous electrolyte secondary battery according to the present invention includes the positive electrode for a non-aqueous electrolyte secondary battery according to the above invention, a negative electrode, a separator, and a non-aqueous electrolyte solution containing a lithium salt and a non-aqueous solvent. [Effects of the Invention]
[0014] According to the present invention, it is possible to obtain a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery that suppress heat generation even when a sudden short circuit occurs. [Brief explanation of the drawings]
[0015] [Figure 1] FIG. 1 is a cross-sectional view illustrating the configuration of a nonaqueous electrolyte secondary battery including a positive electrode for a nonaqueous electrolyte secondary battery according to Embodiment 1 of the present invention. [Figure 2] FIG. 2 is an exploded perspective view illustrating the configuration of a nonaqueous electrolyte secondary battery including a positive electrode for a nonaqueous electrolyte secondary battery according to Embodiment 2 of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0016] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following description. Furthermore, various modifications and improvements can be made to the present embodiments, and such modifications and improvements can also be included in the present invention.
[0017] Although details will be described later, FIG. 1 is a cross-sectional view of a laminate-type nonaqueous electrolyte secondary battery, and FIG. 2 is an exploded perspective view for explaining the configuration of a coin-type nonaqueous electrolyte secondary battery. 1 and 2 show configuration examples of a laminate-type nonaqueous electrolyte secondary battery and a coin-type nonaqueous electrolyte secondary battery as examples of embodiments, but the shape of the nonaqueous electrolyte secondary battery in the present invention is not particularly limited and may be flat, cylindrical, prismatic, coin-type, etc. Furthermore, the exterior body of the nonaqueous electrolyte secondary battery is not particularly limited either and known materials such as laminate film, aluminum, aluminum alloy, and stainless steel can be used.
[0018] (Embodiment 1) Fig. 1 is a cross-sectional view illustrating the configuration of a nonaqueous electrolyte secondary battery including a positive electrode for a nonaqueous electrolyte secondary battery according to embodiment 1 of the present invention. The nonaqueous electrolyte secondary battery 1 shown in Fig. 1 is a stacked-type nonaqueous electrolyte secondary battery formed by stacking a plurality of pairs of a positive electrode, a negative electrode, and a separator.
[0019] The non-aqueous electrolyte secondary battery 1 includes a bag-shaped exterior body 2 made of laminate film. An electrode group 3 having a laminated structure is housed within the exterior body 2. The laminate film has a structure in which, for example, multiple (e.g., two) plastic films are stacked together with a metal foil such as aluminum foil sandwiched between adjacent plastic films. One of the two plastic films is a heat-sealable resin film. The exterior body 2 is made by stacking two laminate films with the heat-sealable resin films facing each other, and houses the electrode group 3 and non-aqueous electrolyte between these laminate films. The two laminate film portions around the electrode group 3 are heat-sealed to each other to seal, thereby hermetically housing the electrode group 3 and non-aqueous electrolyte.
[0020] The electrode group 3 has a positive electrode 4, a negative electrode 5, a separator 6, a positive electrode lead 7, a positive electrode tab 8, a negative electrode lead 9, and a negative electrode tab 10. The separator 6 is interposed between the positive electrode 4 and the negative electrode 5. The electrode group 3 has a multi-layer structure in which the negative electrode 5 is located as the outermost layer and the separator 6 is located between the negative electrode 5 and the inner surface of the exterior body 2.
[0021] The positive electrode 4 is composed of a positive electrode current collector 41 and a positive electrode mixture layer 42 formed on one or both surfaces of the positive electrode current collector 41 .
[0022] The positive electrode current collector 41 is made of aluminum, nickel, stainless steel, titanium, other alloys, etc. Among these, it is preferable to use aluminum from the viewpoint of electronic conductivity and battery operating potential.
[0023] The positive electrode mixture layer 42 includes a first positive electrode active material, a second positive electrode active material, a conductive material, and a binder. The first and second positive electrode active materials are each capable of absorbing and desorbing lithium.
[0024] The first positive electrode active material is a layered compound represented by the general formula shown in the following formula (1). The layered compound is a lithium (Li) - nickel (Ni) - cobalt (Co) - containing composite metal oxide in which sheet - like particles form layers. Li a Ni x Co y M1 1-x-y O2···(1) However, in the general formula (1), M1 is at least one selected from titanium (Ti), zirconium (Zr), niobium (Nb), tungsten (W), phosphorus (P), aluminum (Al), magnesium (Mg), vanadium (V), manganese (Mn), calcium (Ca), strontium (Sr), chromium (Cr), iron (Fe), boron (B), gallium (Ga), indium (In), silicon (Si), molybdenum (Mo), yttrium (Y), tin (Sn), copper (Cu), silver (Ag), cerium (Ce), praseodymium (Pr), germanium (Ge), bismuth (Bi), barium (Ba), erbium (Er), lanthanum (La), samarium (Sm), ytterbium (Yb), antimony (Sb), bismuth (Bi), sulfur (S) and zinc (Zn), and satisfies 0 < a ≤ 1.2, 0 < x ≤ 0.9, 0 < y ≤ 0.5, 0 < x + y < 1.
[0025] The second positive electrode active material is a compound represented by the general formula shown in the following formula (2), and a film made of a carbon material is formed on the surface of a phosphate compound (olivine - type compound) having an olivine structure. LiMn z M2 b Fe 1-z-b PO4···(2) However, in the general formula (2), M2 is at least one selected from nickel (Ni), cobalt (Co), titanium (Ti), copper (Cu), zinc (Zn), magnesium (Mg), zirconium (Zr), calcium (Ca), yttrium (Y), molybdenum (Mo), barium (Ba), lead (Pb), bismuth (Bi), lanthanum (La), cerium (Ce), neodymium (Nd), gadolinium (Gd), aluminum (Al), gallium (Ga), and strontium (Sr), and satisfies 0 < z ≦ 0.9, 0 ≦ b ≦ 0.1, and 0 < z + b < 1.
[0026] The carbon material is a conductive carbon material. The second positive electrode active material has at least a part of the surface of at least some of the primary particles coated with a carbon material by a film composed of the carbon material present on the surface of the second positive electrode active material. The purity of carbon and the thickness of the carbon film can be arbitrarily selected, but it is preferably controlled such that the ratio of the weight of the carbon material to the weight of the entire second positive electrode active material is 0.1% or more and 5% or less.
[0027] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation, the positive electrode 4 has a peak width at half maximum P1 attributable to the (003) plane of the first positive electrode active material, where the diffraction angle (2θ) between the direction of the incident X-ray and the direction of the diffracted X-ray is in the range of 18.0° to 19.0°, and a peak width at half maximum P2 attributable to the (101) plane of the second positive electrode active material, where the diffraction angle (2θ) is in the range of 20.0° to 21.0°, where P1 / P2 is 0.30 to 1.00. It is known that P1 and P2 are inversely proportional to the crystallite diameters (primary particle diameters) of the first and second positive electrode active materials, respectively. The reason for focusing on the peaks attributable to the (003) plane of the first positive electrode active material and the (101) plane of the second positive electrode active material in the present invention is that, due to their crystalline structures (layered structure, olivine structure), these peaks have higher intensities than other peaks and are less likely to be confused with nearby peaks, making it easier to accurately measure the half-width. Furthermore, regardless of the type of positive electrode active material, the smaller the crystallite size, the higher the lithium ion diffusivity within the active material particles. Therefore, a larger ratio P1 / P2 indicates that the lithium ion diffusivity of the first positive electrode active material is likely to be higher than that of the second positive electrode active material. When the ratio P1 / P2 is greater than 1.00, the lithium ion diffusivity of the first positive electrode active material is too high compared to that of the second positive electrode active material, which makes the first positive electrode active material more likely to react preferentially when a short circuit occurs, leading to heat generation due to thermal runaway. If the ratio P1 / P2 is set to less than 0.30, the crystallite size of the second positive electrode active material must be made extremely small, which would result in extremely low crystallinity of the second positive electrode active material, making the synthesis of the material itself difficult. Note that Cu-Kα radiation is Kα radiation generated using copper (Cu) as a target. Furthermore, X-ray diffraction measurements are performed using a positive electrode before assembly into a nonaqueous electrolyte secondary battery, or a positive electrode of a nonaqueous electrolyte secondary battery with a state of charge (SOC) of 0% after initial activation treatment through at least one charge / discharge cycle.
[0028] The tap density of the second positive electrode active material is preferably 0.7 g / cc or more and 1.00 g / cc or less, and more preferably 0.8 g / cc or more. When the tap density is 1.00 g / cc or less, the primary particles of the second positive electrode active material do not form high-density granules or secondary particles but have a bulky shape. This allows the second positive electrode active material to surround the first positive electrode active material more tightly than conventional materials. This is thought to reduce the exothermic reaction caused by direct contact between the first positive electrode active material and the nonaqueous electrolyte in the event of a short circuit. As a result, heat generation due to thermal runaway during a short circuit can be suppressed. This not only reduces the temperature rise of the nonaqueous electrolyte secondary battery during a short circuit, but also reduces swelling, cracking, and rupture due to electrolyte decomposition on the surface of the first positive electrode active material due to temperature rise. On the other hand, if the tap density is greater than 1.00 g / cc, the second positive electrode active material is granulated at a high density, which is thought to make it difficult for the second positive electrode active material to surround the first positive electrode active material. This makes it difficult to prevent the temperature rise of the nonaqueous electrolyte secondary battery during a short circuit, and makes swelling, cracking, and explosion more likely to occur. Furthermore, if the tap density is less than 0.7 g / cc, the dispersibility of the second positive electrode active material during the preparation of the slurry for the positive electrode mixture layer 42 is reduced, making it more likely to aggregate, which induces streaks during the preparation of the positive electrode, making it difficult to produce a positive electrode of uniform quality. Furthermore, if the tap density is 0.8 g / cc or greater, the dispersibility of the second positive electrode active material during the preparation of the slurry is improved.
[0029] The median diameter of the second positive electrode active material is preferably 1 / 100 to 1 / 5 of the median diameter of the first positive electrode active material. Furthermore, the median diameter of the second positive electrode active material is preferably 0.1 μm to 1.0 μm. Satisfying these requirements allows the second positive electrode active material to surround the first positive electrode active material more tightly than conventional materials, which is believed to further suppress heat generation due to thermal runaway during short circuit. This not only reduces the temperature rise of the nonaqueous electrolyte secondary battery during short circuit, but also reduces swelling, cracking, and rupture due to electrolyte decomposition on the surface of the first positive electrode active material caused by temperature rise. If the median diameter of the second positive electrode active material is significantly smaller than that of the first positive electrode active material, the second positive electrode active material's dispersibility during slurry preparation for the positive electrode mixture layer 42 decreases, making it more likely to aggregate, leading to streaks during positive electrode fabrication and making it difficult to fabricate positive electrodes of uniform quality. Furthermore, if the median diameter of the second positive electrode active material is less than 0.1 μm, the crystallinity of the second positive electrode active material itself tends to be extremely low, making material synthesis itself difficult. If the median diameter of the second positive electrode active material is 1 / 20 or more (1 / 5 or less) of the median diameter of the first positive electrode active material, or if the median diameter of the second positive electrode active material is 0.5 μm or more, the dispersibility of the second positive electrode active material during slurry preparation is improved. Note that, in this specification, the median diameter may also be referred to as D50.
[0030] Furthermore, the weight ratio of the second positive electrode active material to the total weight of the first positive electrode active material and the second positive electrode active material is preferably 10% or more and 30% or less. If the weight ratio of the second positive electrode active material exceeds 30%, the charge / discharge curve of the nonaqueous electrolyte secondary battery 1 tends to have more steps (the number of inflection points increases), making it difficult to estimate the depth of charge and state of degradation from the voltage and current values during charge / discharge, reducing practicality. Furthermore, if the weight ratio of the second positive electrode active material is less than 10%, it is thought that the second positive electrode active material will have difficulty sufficiently surrounding the first positive electrode active material.
[0031] The above-mentioned median diameter and tap density refer to values in the positive electrode mixture layer 42 after the nonaqueous electrolyte secondary battery has been fabricated. However, these values are generally equivalent to the median diameter and tap density of the first positive electrode active material and the second positive electrode active material before the positive electrode is fabricated. Therefore, if the median diameter and tap density values of the first positive electrode active material and the second positive electrode active material before fabrication satisfy the requirements of the present invention, the fabricated positive electrode can be considered to also satisfy the requirements of the present invention.
[0032] Whether the median diameter and tap density of the first and second positive electrode active materials in the fabricated positive electrode mixture layer satisfy the requirements of the present invention can be confirmed, for example, by the following method. The nonaqueous electrolyte secondary battery is disassembled in an argon-filled glove box to remove the positive electrode 4. The positive electrode 4 is washed with an appropriate solvent (e.g., dimethyl carbonate) and then vacuum-dried to remove the solvent. The positive electrode is then immersed in a solvent such as N-methyl-2-pyrrolidone and subjected to ultrasonic waves to separate the positive electrode mixture layer 42 from the positive electrode current collector 41. The solvent in which the separated positive electrode mixture layer 42 is dispersed is centrifuged to separate the various substances in the positive electrode mixture layer 42. The median diameter of the separated first and second positive electrode active materials can be measured, for example, by laser diffraction / scattering. The tap density can be measured by, for example, placing the materials in a container, tapping the container, and measuring the weight divided by the volume of the particles. The nonaqueous electrolyte secondary battery used above may have been subjected to initial activation or charge / discharge cycling in any step, and it is preferable to set the charge rate of the nonaqueous electrolyte secondary battery to 0% beforehand when removing the positive electrode 4.
[0033] The conductive material assists electron conduction in the positive electrode. The conductive material is not particularly limited, and known materials can be used. Examples of conductive materials include conductive carbon powders such as acetylene black and carbon black such as ketjen black, carbon nanotubes, carbon nanofibers, graphene, activated carbon, and graphite. The conductive material may be made of a single material or multiple materials (e.g., a first conductive material and a second conductive material).
[0034] The binder binds the positive electrode current collector, the positive electrode active material, and the conductive material. There are no particular limitations on the binder, and known or commercially available binders can be used. Examples of binders include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and styrene-butadiene rubber (Styrene-Butadiene Examples of the rubber include SBR, butadiene rubber, polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), butyl rubber, poly(meth)acrylate (PMMA), polyethylene oxide (PEO), polypropylene oxide (PO), polyepichlorohydrin, polyphosphazene, polyacrylonitrile, hexafluoropropylene (HFP), and copolymers thereof, or a mixture of two or more thereof.
[0035] The negative electrode 5 is composed of a negative electrode current collector 51 and a negative electrode mixture layer 52 containing a negative electrode active material formed on one or both surfaces of the negative electrode current collector 51 or metallic lithium (not shown).
[0036] Although there is no particular limitation on the negative electrode current collector 51, it is preferable to use a metal. Suitable metals include aluminum foil and copper, and depending on the application, a porous aluminum current collector may also be used. Among these, copper is preferable from the viewpoint of electronic conductivity and battery operating potential.
[0037] The negative electrode mixture layer 52 is made of, for example, lithium, a lithium alloy, a titanium-niobium alloy, or a material such as graphite, amorphous carbon, or a transition metal composite oxide (e.g., Li4Ti5O 12 The negative electrode mixture layer 52 contains at least one active material selected from the group consisting of titanium dioxide (TiNb2O7, TiNb2O7, etc.), an alloy capable of absorbing and releasing lithium, and silicon. Among these, graphite is preferred because it has an operating potential very close to that of metallic lithium, allows charging and discharging at a high operating voltage, and has excellent cycle characteristics. Graphite may also be used in combination with other negative electrode active materials. The negative electrode mixture layer 52 also contains a conductive material and a binder. The conductive material and binder may be the same materials as those used in the positive electrode 4.
[0038] The separator 6 is disposed between the positive electrode and the negative electrode and has a porosity that allows the components of the non-aqueous electrolyte to pass through. The separator 6 is formed, for example, using a porous sheet separator made of polymer or fiber, a nonwoven fabric separator, or the like. The separator 6 may be made of a material such as polyethylene, polypropylene, aramid, or polyimide, or may have multiple layers of different materials including these. However, from the viewpoint of providing a shutdown function in the event of heat generation, it is preferable that the separator 6 has a layer containing polyethylene. The pore size of the separator 6 is preferably 0.01 to 10 μm, and the thickness is preferably 5 to 30 μm. The separator 6 may also be formed by laminating a ceramic layer as a heat-resistant insulating layer on a porous substrate. When a solid electrolyte is used as the non-aqueous electrolyte, the separator 6 may not be present.
[0039] The positive electrode leads 7 extend downward from the positive electrode mixture layer 42, for example, as shown in FIG. 1. As an example, each positive electrode lead 7 is a portion of the positive electrode current collector 41 that is not coated with the positive electrode mixture layer 42. The positive electrode leads 7 are bundled and joined to each other at the end opposite to the positive electrode mixture layer 42 side within the exterior body 2.
[0040] One end of the positive electrode tab 8 is joined to the positive electrode lead 7, and the other end extends to the outside through the sealing portion of the exterior body 2.
[0041] The negative electrode leads 9 each extend upward from the negative electrode mixture layer 52, for example, as shown in FIG. 1. They may extend in the same direction as the positive electrode lead 7, provided that they do not come into contact with the positive electrode lead 7. As an example, each negative electrode lead 9 is a portion of the negative electrode current collector 51 that is not coated with the negative electrode mixture layer 52. The negative electrode leads 9 are bundled and joined to each other at the end opposite to the negative electrode mixture layer 52 side within the exterior body 2.
[0042] One end of the negative electrode tab 10 is joined to the negative electrode lead 9, and the other end passes through the sealing portion of the exterior body 2 and extends to the outside.
[0043] The nonaqueous electrolyte may be a nonaqueous electrolytic solution or a solid electrolyte. The following describes the nonaqueous electrolytic solution in particular. The nonaqueous electrolytic solution is enclosed within the exterior body 2. The nonaqueous electrolytic solution injection portion of the exterior body 2 is sealed after the nonaqueous electrolytic solution is injected. The nonaqueous electrolytic solution contains an electrolyte and a nonaqueous solvent.
[0044] The electrolyte is not particularly limited, and any lithium salt commonly used in non-aqueous electrolyte secondary batteries can be used. For example, LiPF, LiAsF, LiBF, LiCF, SO, LiN(C m F 2m+1 SO2)(C n F 2n+1 SO2) (m and n are integers of 1 or more), LiC(C p F 2p+1 SO2)(C q F 2q+1 SO2)(C r F 2r+1Examples of electrolytes that can be used include lithium difluoro(oxalato)borate (SO2) (p, q, and r are integers of 1 or greater), lithium difluoro(oxalato)borate, and lithium bis(oxalato)borate. These electrolytes may be used alone or in combination of two or more. From the viewpoints of lithium ion conductivity, the viscosity of the electrolyte, and the temperature characteristics of conductivity, the electrolyte should preferably have a concentration of 0.1 to 3 mol / L, and preferably 0.5 to 1.5 mol / L.
[0045] The non-aqueous solvent contains a cyclic carbonate and / or a chain carbonate as a main component. The cyclic carbonate is preferably at least one selected from ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). The chain carbonate is preferably at least one selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The cyclic carbonate is related to the degree of dissociation of the electrolyte components, and the chain carbonate is related to the viscosity of the electrolyte solution.
[0046] In addition, additives other than the lithium salts may be included for the purpose of forming a high-quality coating on the surface of the negative electrode active material through reductive decomposition during charge and discharge. The additives are not particularly limited, but examples include vinylene carbonate, fluoroethylene carbonate, 1,3,2-dioxathiolane 2,2-dioxide (MMDS), 1,5,2,4-dioxadithiane 2,2,4,4-tetraoxide, tris(trimethylsilyl) phosphite, 1-propene 1,3-sultone, and Li2PO2F2. These additives may be used alone or in combination. They may also be used in combination with other additives. Furthermore, other additives may also be used alone.
[0047] In the present embodiment 1, in the positive electrode 4 of the nonaqueous electrolyte secondary battery 1, the positive electrode mixture layer 42 has a first positive electrode active material represented by general formula (1) and a second positive electrode active material containing a compound represented by general formula (2), and in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation on the positive electrode before assembly into a nonaqueous electrolyte secondary battery or the positive electrode of the nonaqueous electrolyte secondary battery after initial activation treatment by at least one charge / discharge cycle when the SOC is 0%, the ratio P1 / P2 of the half-value width P1 of the peak assigned to the (003) plane of the first positive electrode active material to the half-value width P2 of the peak assigned to the (101) plane of the second positive electrode active material is set to be 0.30 or more and 1.00 or less. By satisfying the above conditions and making the crystallite diameter of the first positive electrode active material larger than that of the second positive electrode active material, the lithium diffusibility of the first positive electrode active material is prevented from becoming higher than that of the second positive electrode active material. In the first embodiment, in the event of a short circuit, for example, lithium ions are less likely to diffuse into the first positive electrode active material in the positive electrode mixture layer 42, thereby suppressing thermal decomposition of the first positive electrode active material. According to the first embodiment, it is possible to obtain a positive electrode 4 and a nonaqueous electrolyte secondary battery 1 that suppress heat generation even when a sudden short circuit occurs.
[0048] (Embodiment 2) 2 is an exploded perspective view illustrating the configuration of a nonaqueous electrolyte secondary battery including a positive electrode for a nonaqueous electrolyte secondary battery according to Embodiment 2 of the present invention. Nonaqueous electrolyte secondary battery 1A includes case 110, leaf spring 111, positive electrode current collector 112, positive electrode mixture layer 113, separator 114, negative electrode 115, gasket 116, and cap 117. Positive electrode current collector 112 and positive electrode mixture layer 113 form positive electrode 118.
[0049] In the nonaqueous electrolyte secondary battery 1A, the case 110 and the cap 117 are fixed together by crimping or the like, and the battery is filled with a nonaqueous electrolyte. The nonaqueous electrolyte secondary battery 1A is liquid-tightly sealed by the case 110, the gasket 116, and the cap 117. The positive electrode current collector 112, the positive electrode mixture layer 113, the separator 114, and the negative electrode 115 are biased toward the cap 117 by the leaf spring 111. This keeps the components in close contact with each other.
[0050] The positive electrode current collector 112 is made of the same material as the positive electrode current collector 41 . The positive electrode mixture layer 113 has the same configuration as the positive electrode mixture layer 42 .
[0051] Separator 114 is a porous disk-shaped material and is provided between positive electrode 115 and negative electrode 115. Separator 114 has the same structure as separator 6.
[0052] The nonaqueous electrolyte may be the same as that of the first embodiment.
[0053] The negative electrode 115 has the same configuration as the negative electrode 5 .
[0054] In the present second embodiment, in the positive electrode 118 of the nonaqueous electrolyte secondary battery 1A, the positive electrode mixture layer 113 has a first positive electrode active material represented by general formula (1) and a second positive electrode active material containing a compound represented by general formula (2), and in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation on the positive electrode before assembly into a nonaqueous electrolyte secondary battery or on the positive electrode of the nonaqueous electrolyte secondary battery after initial activation treatment by at least one charge-discharge cycle when the SOC is 0%, the ratio P1 / P2 of the half-width P1 of the peak attributable to the (003) plane of the first positive electrode active material to the half-width P2 of the peak attributable to the (101) plane of the second positive electrode active material is set to be 0.30 or more and 1.00 or less. According to the present second embodiment, as in the first embodiment, it is possible to obtain the positive electrode 118 and the nonaqueous electrolyte secondary battery 1A that suppress heat generation even when a sudden short circuit occurs. [Example]
[0055] The present invention will be described in more detail below by way of examples, but the present invention is not limited to the following examples in any way.
[0056] <How to make the positive electrode> LiNi as the first positive electrode active material 0.5 Co 0.2 Mn 0.3 O2(NCM) 75.2 wt% and LiMn as the second positive electrode active material. 0.7 Fe 0.3 A positive electrode active material slurry was prepared by mixing 18.8 wt% of PO4 (LMFP), 2 wt% of graphite as a first conductive material, 3 wt% of acetylene black as a second conductive material, 1 wt% of polyvinylidene fluoride (PVDF) as a binder, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) as a viscosity adjusting solvent.
[0057] The obtained positive electrode active material slurry was applied to both sides of a 20 μm thick aluminum foil serving as a positive electrode current collector, and then dried to form a positive electrode mixture layer. The amount of the positive electrode mixture layer applied per side was 99 g / m. 2 Next, the positive electrode was subjected to press working to set the density of the positive electrode mixture layer to 2.7 g / cm. 3 Thereafter, the positive electrode mixture layer was applied to the rectangular portion of the positive electrode sheet, and the uncoated portion was cut so as to protrude in a rectangular shape as a positive electrode lead from one side of the rectangular portion coated with the positive electrode mixture layer. The protruding portion was not formed with the positive electrode mixture layer and functioned as a positive electrode lead.
[0058] <Method for producing the negative electrode> A negative electrode active material slurry was prepared by mixing 96.7 wt % graphite as the negative electrode active material, 0.3 wt % acetylene black as the conductive material, 1.5 wt % styrene butadiene rubber as the binder, 1.5 wt % carboxymethyl cellulose as the thickener, and an appropriate amount of ion-exchanged water as the viscosity adjusting solvent.
[0059] The prepared negative electrode active material slurry was applied to both sides of a 10 μm thick copper foil as a negative electrode current collector and dried to form a negative electrode mixture layer, thereby producing a negative electrode. The coating amount of the negative electrode mixture layer per side was 58 g / m. 2 Next, the negative electrode was subjected to press working to set the density of the negative electrode mixture layer to 1.2 g / cm 3 Thereafter, the negative electrode mixture layer was formed on the rectangular portion, and the uncoated portion was cut so as to protrude in a rectangular shape from one side of the rectangular portion on which the negative electrode mixture layer was formed. The protruding portion was not formed with the negative electrode mixture layer and functioned as a negative electrode lead.
[0060] <Preparation of non-aqueous electrolyte> A non-aqueous electrolyte solution was prepared by dissolving 1.3 mol / L of LiPF6 as a lithium salt and 3 wt% of vinylene carbonate as an additive in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 2:5:3.
[0061] <Fabrication of electrode element> Next, an electrode element was fabricated by alternately stacking positive electrodes with positive collector leads and negative electrodes with negative collector leads on a zigzag-like separator. The separator consisted of a polyethylene substrate layer with polypropylene surface layers on both sides (PE / PP / PE). The separator was 20 μm thick. The positive and negative electrode leads were then bundled together, and the positive electrode terminal was connected to the bundled positive lead by ultrasonic welding. The negative electrode terminal was also connected to the bundled negative lead by ultrasonic welding. The resulting electrode element had a thickness of 3.0 mm and a rated capacity of 4.8 Ah. The "rated capacity" here refers to the discharge capacity measured when a constant-current-constant-voltage charge (cutoff current: 0.05 C) was performed at an upper voltage of 4.2 V and a current value of 0.5 C, followed by a constant-current discharge at a lower voltage of 2.7 V and a current value of 0.2 C.
[0062] <Fabrication of Non-Aqueous Electrolyte Secondary Battery> Two laminate films were prepared as exterior bodies, each having a structure in which a heat-sealable resin layer made of polyolefin, a metal layer made of aluminum foil, and a protective layer made of nylon resin and polyester resin were laminated in this order. The heat-sealable resin layers of the two laminate films were arranged facing each other, and the laminate films were overlapped with their adhesive surfaces facing each other so that electrode groups could be accommodated in the two accommodating recesses. The electrode groups were arranged so that the portions where the heat-sealable resin parts of each terminal were formed passed between the edges of the two laminate films, leaving a portion of each terminal exposed to the outside. In this state, the heat-sealable resin layers of the laminate films were heat-sealed along the three edges, including the two edges from which the tabs of the laminate films extended. Next, the electrolyte solution prepared above was injected into the one edge of the exterior body that was not heat-sealed. Next, the remaining edge of the exterior body was heat-sealed under reduced pressure to produce a nonaqueous electrolyte secondary battery (cell).
[0063] <Measuring half-width> For the positive electrode before assembly into a non-aqueous electrolyte secondary battery, the X-ray diffraction pattern of the fabricated positive electrode obtained by X-ray diffraction measurement using Cu-Kα radiation was measured to measure the half-value width P1 of the peak attributable to the (003) plane of NCM in the diffraction angle (2θ) range of 18.0° to 19.0°, and the half-value width P2 of the peak attributable to the (101) plane of LMFP in the diffraction angle (2θ) range of 20.0° to 21.0°.
[0064] <Tap density> As specified in JIS standard Z2504:2020, powdered LMFP was placed in a container. The container was then tapped 100 times to measure the weight divided by the volume of the particles to fill the gaps between them, and this value was used as the tapped density. A shaking specific gravity meter was used for the measurement.
[0065] <Particle size measurement> The median diameter of NCM and LMFP was the particle size (D50) at which the relative particle amount was 50%, as measured by the laser diffraction / scattering method described in JIS standard Z8825: 2013. The measurement was performed using a laser diffraction particle size distribution analyzer SALD-2300 (Shimadzu Corporation).
[0066] <Nail penetration test> The fabricated nonaqueous electrolyte secondary battery (cell) was previously subjected to constant-current / constant-voltage charging (cutoff current: 0.05C) with a maximum voltage of 4.2V and a current value of 0.5C. A stainless steel nail (3mm diameter) was driven into the center of the cell at a nail penetration rate of 0.1mm / s and a nail penetration depth of 3.0mm, just before penetration. The maximum cell surface temperature (hereafter referred to as "surface temperature") after nail penetration was measured. The cell's appearance was also inspected one hour after nail penetration to confirm the presence of cracks other than the nail penetration area. This test was based on the international standard IEC TR 62660-4, but the nail penetration depth was increased to facilitate heat generation, resulting in a simultaneous short circuit of more positive and negative electrodes. This test simulated a very severe short circuit condition.
[0067] Example 1 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The ratio of the half-widths of NCM and LMFP (hereinafter simply referred to as the "ratio") (P1 / P2) was 0.65. After a nail penetration test, the cell did not split, and the surface temperature was 78°C. [Table 1]
[0068] Example 2 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P1) was 0.274 degrees and the D50 of the NCM was 0.90 μm. The ratio (P1 / P2) was 0.97. After a nail penetration test, the cell did not split, and the surface temperature was 85°C.
[0069] Example 3 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P2) was 0.354 degrees, the tap density of the LMFP was 0.89 g / cc, and the D50 of the LMFP was 0.50 μm. The ratio (P1 / P2) was 0.52. After a nail penetration test, the cell did not split, and the surface temperature was 83°C.
[0070] Example 4 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P2) was 0.367 degrees, the tap density of the LMFP was 1.04 g / cc, and the D50 of the LMFP was 1.00 μm. The ratio (P1 / P2) was 0.50. After a nail penetration test, the cell split open, and the surface temperature was 99°C.
[0071] Example 5 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P2) was 0.316 degrees, the tap density of the LMFP was 0.76 g / cc, and the D50 of the LMFP was 0.80 μm. The ratio (P1 / P2) was 0.58. After a nail penetration test, the cell did not split, and the surface temperature was 84°C.
[0072] Example 6 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1 except that the full width at half maximum P1 was 0.233 degrees and the D50 of the NCM was 4.3 μm. The ratio (P1 / P2) was 0.83. After a nail penetration test, the cell split open and the surface temperature was 110°C.
[0073] Example 7 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P1) was 0.249 degrees and the D50 of the NCM was 4.9 μm. The ratio (P1 / P2) was 0.88. After a nail penetration test, the cell did not split, and the surface temperature was 88°C.
[0074] Example 8 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum P1 was 0.252 degrees, the full width at half maximum P2 was 0.255 degrees, the tap density of the LMFP was 0.91 g / cc, the D50 of the NCM was 21.3 μm, and the D50 of the LMFP was 1.50 μm. The ratio (P1 / P2) was 0.99. After a nail penetration test, the cell split open, and the surface temperature was 123°C.
[0075] Example 9 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The procedure was the same as in Example 1, except that the proportion of LMFP was 30%. The ratio (P1 / P2) was 0.65. After a nail penetration test, the cell did not split, and the surface temperature was 69°C.
[0076] Example 10 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The procedure was the same as in Example 1, except that the proportion of LMFP was 10%. The ratio (P1 / P2) was 0.65. After a nail penetration test, the cell did not split, and the surface temperature was 92°C.
[0077] Example 11 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The procedure was the same as in Example 1, except that the proportion of LMFP was 5%. The ratio (P1 / P2) was 0.65. After a nail penetration test, the cell split open, and the surface temperature was 137°C.
[0078] Example 12 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P2) was 0.371 degrees, the tap density of the LMFP was 0.69 g / cc, and the D50 of the LMFP was 0.80 μm. The ratio (P1 / P2) was 0.50. After a nail penetration test, the cell did not split, and the surface temperature was 87°C. However, the positive electrode had numerous streaks, making it unsuitable for continuous production and industrially undesirable.
[0079] Example 13 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The half-value width P1 was 0.223 degrees, the half-value width P2 was 0.354 degrees, the tap density of the LMFP was 0.89 g / cc, the D50 of the NCM was 51.4 μm, and the D50 of the LMFP was 0.50 μm. The battery was the same as in Example 1. The ratio (P1 / P2) was 0.63. After a nail penetration test, the cell did not crack, and the surface temperature was 74°C. However, the positive electrode had numerous streaks, making it unsuitable for continuous production and industrially undesirable.
[0080] Example 14 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P2) was 0.304 degrees, the tap density of the LMFP was 1.03 g / cc, and the D50 of the LMFP was 2.60 μm. The ratio (P1 / P2) was 0.61. After a nail penetration test, the cell split open, and the surface temperature was 140°C.
[0081] Example 15 A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum P1 was 0.250 degrees, the full width at half maximum P2 was 0.255 degrees, the tap density of the LMFP was 1.10 g / cc, the D50 of the NCM was 4.3 μm, and the D50 of the LMFP was 3.60 μm. The ratio (P1 / P2) was 0.98. After a nail penetration test, the cell split open, and the surface temperature was 152°C.
[0082] (Comparative Example 1) A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P1) was 0.393 degrees, the tap density of the LMFP was 0.91 g / cc, and the D50 of the NCM was 6.2 μm. The ratio (P1 / P2) was 1.39. After a nail penetration test, the cell split open, and the surface temperature was 486°C.
[0083] (Comparative Example 2) A nonaqueous electrolyte secondary battery was fabricated using a positive electrode having the physical properties shown in Table 1 as the positive electrode mixture layer. The battery was the same as in Example 1, except that the full width at half maximum (P2) was 0.178 degrees, the tap density of the LMFP was 0.93 g / cc, and the D50 of the LMFP was 1.00 μm. The ratio (P1 / P2) was 1.03. After a nail penetration test, the cell split open, and the surface temperature was 505°C.
[0084] If the ratio (P1 / P2) were to be less than 0.30, the crystallite size of the second positive electrode active material would have to be extremely small, which would make the crystallinity of the second positive electrode active material extremely low, making the synthesis of the material itself difficult. Therefore, we did not attempt to achieve a ratio (P1 / P2) of less than 0.30.
[0085] As shown in Table 1, in Examples 1 to 15, the surface temperature after nail penetration was 152°C or lower. On the other hand, in Comparative Examples 1 and 2, the cells split and the surface temperature was as high as 486°C or higher. It is believed that in Comparative Examples 1 and 2, separator meltdown occurred, causing a short circuit inside the cell and resulting in a chain reaction of heat generation. From these results, it can be said that Examples 1 to 15 suppressed heat generation even when a sudden short circuit occurred and have thermal stability. Among them, Examples 1 to 3, 5, 7, 9, and 10 did not pose any industrial problems and no cell splitting was observed, and therefore have particularly excellent thermal stability. [Explanation of symbols]
[0086] 1, 1A non-aqueous electrolyte secondary battery 2. Exterior body 3 electrode groups 4, 118 positive electrode 5, 115 negative electrode 6, 114 Separator 7 Positive lead 8 Positive tab 9 Negative lead 10 Negative electrode tab 41, 112 Positive electrode current collector 42, 113 Positive electrode mixture layer 51 Negative electrode current collector 52 negative electrode mixture layer 110 cases 111 Leaf spring 116 Gasket 117 Cap
Claims
1. A positive electrode for a non-aqueous electrolyte secondary battery, comprising: a positive electrode current collector; and a positive electrode mixture layer formed on a surface of the positive electrode current collector, The positive electrode mixture layer is a first positive electrode active material that is a layered compound represented by the following general formula (1); Li a Ni x Co y M1 1-x-y O 2 (where 0<a≦1.2, 0<x≦0.9, 0<y≦0.5, 0<x+y<1) ... (1) a second positive electrode active material in which a coating film made of a carbon material is formed on a surface of a phosphate compound having an olivine structure, the second positive electrode active material being represented by the following general formula (2): LiMn z M2 b Fe 1-z-b P.O. 4 (where 0<z≦0.9, 0≦b≦0.1, 0<z+b<1) ... (2) A conductive material; Including, In an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu—Kα radiation on the positive electrode for a non-aqueous electrolyte secondary battery before assembly into a non-aqueous electrolyte secondary battery, or on the positive electrode for a non-aqueous electrolyte secondary battery after initial activation treatment by at least one charge / discharge cycle when the charge rate of the non-aqueous electrolyte secondary battery is 0%, a ratio P1 / P2 of a first half-width P1 of a peak attributable to a (003) plane of the first positive electrode active material having a diffraction angle of 18.0° or more and 19.0° or less to a second half-width P2 of a peak attributable to a (101) plane of the second positive electrode active material having a diffraction angle of 20.0° or more and 21.0° or less is 0.30 or more and 1.00 or less. A positive electrode for a non-aqueous electrolyte secondary battery. In the above formula (1), M1 is at least one selected from Ti, Zr, Nb, W, P, Al, Mg, V, Mn, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, Cu, Ag, Ce, Pr, Ge, Bi, Ba, Er, La, Sm, Yb, Sb, Bi, S, and Zn; In the above formula (2), M2 is at least one selected from Ni, Co, Ti, Cu, Zn, Mg, Zr, Ca, Y, Mo, Ba, Pb, Bi, La, Ce, Nd, Gd, Al, Ga, and Sr.
2. The second positive electrode active material has a tap density of 0.7 g / cc or more and 1.00 g / cc or less.
2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1.
3. the median diameter of the second positive electrode active material is 1 / 100 or more and 1 / 5 or less of the median diameter of the first positive electrode active material; 3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2.
4. The median diameter of the second positive electrode active material is 0.1 μm or more and 1.0 μm or less.
4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1.
5. a ratio of the weight of the second positive electrode active material to the total weight of the first positive electrode active material and the second positive electrode active material is 10% or more and 30% or less; 5. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1.
6. The positive electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5, a negative electrode; A separator; a non-aqueous electrolyte solution containing a lithium salt and a non-aqueous solvent; A non-aqueous electrolyte secondary battery comprising:
Citation Information
Patent Citations
Analog*digital converter with check function in fail safe
JP1980074239A
Positive electrode active material and secondary battery including the same
JP2014075352A
Lithium-ion battery with improved thermal stability
JP2018500737A
Mixed positive electrode active material for lithium ion secondary battery and production method of the same
JP2020031028A
Lithium-ion battery with improved thermal stability
JP6813487B2